THE IMPACT OF ONLINE MARKETING STRATEGIES IN INCREASING THE INCOME OF MSMEs ACTORS - Windayani, Windayani (Journal of Finance, Economics and Business, 2024)
Online marketing has become an important strategy for MSMEs in Indonesia to increase revenue, but there are still challenges in its utilization, such as limited digital knowledge and tight market competition. This study aims to analyze the impact of online marketing strategies on increasing MSME revenue, with a focus on visual content, paid promotion on social media, and the use of digital platforms. The method used is a qualitative approach with in-depth interviews with MSMEs in various industrial sectors. The results of the study indicate that the use of attractive visual content and paid promotion on social media has proven effective in increasing market reach and MSME revenue. However, challenges such as limited knowledge of digital marketing and difficulties in maintaining customer loyalty remain obstacles. The implications of this study suggest that MSMEs improve their digital skills through training and mentoring, and focus on content innovation and product differentiation to face increasingly tight market competition. This study contributes to developing literature on digital marketing in the Indonesian MSME sector.